Prealgebra - Baratto, Stefan; Bergman, Barry; Hutchison, Donald (New York McGraw Hill, 2010)
"Prealgebra, by Baratto, Bergman, and Hutchison is part of the latest offerings in the successful Hutchison Series in Mathematics. The book is designed for a one-semester course in basic math and is appropriate for lecture, learning center, laboratory, and self-paced settings. The ninth edition continues the series' hallmark approach of encouraging mastery of mathematics through careful practice. The text provides detailed, straightforward explanations and accessible pedagogy to help students grow their math skills from the ground up. The authors use a three-pronged approach of communication, pattern recognition, and problem solving to present concepts understandably, stimulate critical-thinking skills, and stress reading and communication skills in order to help students become effective problem-solvers. Features such as Tips for Student Success, Check Yourself exercises, and Activities underscore this approach and the underlying philosophy of mastering math through practice. Exercise sets have been significantly expanded and are now better-organized, and applications are now more thoroughly integrated throughout the text. The text is fully-integrated with McGraw-Hill's online learning system, Connect Math Hosted by ALEKS Corp, and is available with ALEKS 360"--
"Learning math can be an exciting adventure! As you embark on this journey, we are here with you. Whether this material is new to you or you are trying to master topics that previously eluded you, this text is designed to make it easier to learn the essential mathematics that you will need. Learning math, learning to be a student (again), and growing as a person are all intertwined as part of your experience. We hope that you continue to grow as a student and as a person while you grow your math skills from the ground up. We have seen many students succeed in our math classes and we offer you some guidance that may help you to be one of the successful students. Through the fi rst half of this text, we offer a series of Tips for Student Success features. These cover many of those skills and actions that successful college students exhibit. You can fi nd a complete listing of the Tips for Student Success in the Index. We would like to highlight two of the more important items in these Tips. Learning math takes time. Students are expected to study 2 to 3 hours per week, outside of class, for every credit hour in a math course. In order to learn the math necessary to succeed in your course, you will need to make this time commitment. Expect to spend an hour or more every day outside of class learning math. Because of the size of this commitment, you need to schedule your day and week to include these hours"--
Includes index.
Keywords: Algebra; Equations; MATHEMATICS / Algebra / General